Development and characterisation of thermo reversible mucoadhesive moxifloxacin hydrochloride in situ ophthalmic gel - M Dholakia; V Thakkar; N Patel; T Gandhi (Wolters Kluwer Medknow Publications, 2012)
A sustain release thermo reversible in situ gel of Moxifloxacin Hydrochloride using mucoadhesive polymer was prepared. Mucoadhesive polymer was used to obtain an ophthalmic delivery system with improved mechanical and mucoadhesive properties that will provide prolong retention time for treatment of ocular diseases. Developed formulations were evaluated for drug-excipient compatibility study, pH, Clarity, Gelation temperature study, Mucoadhesion properties and in-vitro release studies. Drug-excipient compatibility study was performed by FTIR technique.The individual IR spectra of the pure drug and polymers as well as the combination spectra of the drug and polymer were taken, which indicate no interaction between Moxifloxacin and polymers when compared with infrared spectrum of pure drug as all functional group frequencies were present. The values of other parameters obtained were in acceptable range. In vitro release tests revealed that 98% drug was released from the in situ gel containing 0.5% and 1.00% HPMC in 12 hr. provides prolonged release.